Representation of Lymphocytes in Sinonasal Tissue of Chronic Rhinosinusitis Patients - Putu Lusy Indrawati, L; Arfiana Nurul Fatimah, V; Sianipar, O (KnE Life Sciences, 2019)
Chronic rhinosinusitis is divided into nasal polyp subtype and non-nasal polyp subtype. Among those subtypes, there are different histopathologic patterns. One of the criteria of the histopathological parameter is inflammatory cells pattern in sinonasal tissue which can be assessed by counting lymphocytes in sinonasal tissue. This study aims to describe the representation of lymphocytes in sinonasal tissue of chronic rhinosinusitis patients. This descriptive observational study included 21 chronic rhinosinusitis patients in otolaryngology clinic of Dr. Sardjito Hospital Yogyakarta, Indonesia who had undergone endoscopic sinus surgery during the year 2013 and fulfilled the criteria. Information about sample subtypes was obtained from medical record while data about lymphocytes count in sinonasal tissue was obtained from counting microscopically using the light microscope in 5 zigzag consecutive high-power fields (HPF). Nasal polyp subtype was found in 20 (95.24 %) cases while nonnasal polyp subtype was in 1 case (4.76 %). Representation of lymphocytes in nasal polyp subtype was higher than that in non-nasal polyp subtype. Mean, standard deviation, median, minimum count, and maximum count of tissue lymphocyte in nasal polyp subtype were 78 cells/HPF, 46 cells/HPF, 65 cells/HPF, 25 cells/HPF, and 207 cells/HPF respectively while tissue lymphocyte count in non-nasal polyp subtype was 21 cells/HPF. Using Hellquist classification, the histopathological characteristics of nasal polyp subtype were described. The highest count of tissue lymphocytes was found in Hellquist type IV. Within one disease entity, two subtypes, and four histological types, chronic rhinosinusitis has a highly variable amount of tissue lymphocytes. Keywords: Chronic rhinosinusitis, Histopathology, Lymphocyte(s), Nasal polyps, Hellquist classification.